Pharmacological characterisation of Seseli gracile Waldst. & Kit. (Apiaceae) essential oil - Suručić, Relja; Kundaković-Vasović, Tatjana; Marčetić, Mirjana; Drakul, Dragana; Milenković, Marina; Kovačević, Nada (Vojnosanitetski pregled, 2021)
Background/Aim. Phytochemical and pharmacological investigations of essential oils isolated from plant species of the genus Seseli have been intensified recently. These plant species have long-term use in nutrition and traditional medicine in the treatment of various disorders. Volatile secondary metabolites of Seseli gracile Waldst. & Kit (Apiaceae) have not been pharmacologically examined so far. The aim of the conducted research was to assess the antiradical, antimicrobial and spasmolytic activities of S. gracile essential oil isolated from the aerial parts of the plant. Methods. The antiradical activity was determined using the 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging test, antimicrobial activity using broth microdilution method with standard strains of Gram (+), Gram (-) bacteria and yeast, while spasmolytic activity was evaluated on isolated rat ileum, pre-contracted with a high concentration of potassium. Results. The results showed moderate antiradical (SC50 = 78.60 µg/mL) and good spasmolytic activity (IC50 = 271.4 nL/mL) of S. gracile essential oil. In the range of tested concentrations, minimal inhibitory concentration (MIC) was determined only for the strain of Escherichia coli (500 μg/mL). Conclusion. Results obtained in this study justify the need for further studies to elucidate exact molecular mechanism underlay this spasmolytic effect of S. gracile herb essential oil.
Keywords: apiaceae; oils, volatile; pharmacology; plant extracts; muscle relaxation; antioxidants; anti-infective agents